KUALITAS DAN AKTIVITAS ANTIBAKTERI CINCALOK TERHADAP BAKTERI PATOGEN SELAMA WAKTU FERMENTASI - Ekawati Purwijantiningsih; Kenni Novelia; Fransiskus Sinung Pranata (Program Studi Ilmu Gizi, Jurusan Kesmas Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2020)
Cincalok is a typical West Kalimantan fermented food made from small shrimp called rebon with addition of rice and salt. Cincalok fermentation is shown by the presence of lactic acid bacteria (LAB) which have ability to be antibacterial against pathogenic bacteria. The ability of LAB to inhibit pathogenic bacteria can be seen from the appearance of the inhibition zone around agar media. Research conducted using cincalok during fermentation on day 0, 7, 14, 21, and 28 to see the ability of inhibition and the viability of LAB in cincalok then also conducted tests that included pH value, total acid, protein, total volatile base (TVB), and organoleptic tests. The result of this research showed that cincalok is able to inhibit the Escherichia coli bacteria with the largest inhibitory zone area on day 14. Fermentation time variation affects the antibacterial activity against E. coli, LAB viability, pH value, total acid, protein content and TVB of cincalok.